Diferensiasi Hukum bagi Penyedia Layanan Over The Top (Studi Perbandingan Indonesia dengan Singapura) - Lana Aulia Afiftania; Nanik Mahmudah; Fauziah Herman Putri (Faculty of Law Hang Tuah University, 2021)
Over the top media service is form of development of internet based technology. Indonesia as an affected country, has not be able to control and manage it. On the other hand, Singapore already has good legal system. The problem is how the differences between Indonesian and Singapore legal system, also how the rule of law can be applied by Indonesia. This research is normative legal research through conceptual approach and statute approach. Discussion result is the difference of legal system in terms of broadcast content restriction dan the tax collection system. Contrary with Indonesia, Singapore has more spesific content restriction. Tax collection system in Indonesia still experiencing a legal vacuum while Singapore collect taxes through a licence ownership system. That difference can be adopted by Indonesia as basis of payment for provider over the top media service.